Wireless Fidelity Network Security Threats (Wi-Fi) - Zulkarnaen, Irfan; R, M Ziran Maulana; Syarifudin, Syarifudin; Rinaldi, Sebastian; Akem, Umar (JERIT: Journal of Educational Research and Innovation Technology, 2025)
The advancement of wireless network technology has improved communication efficiency but also increased the risk of data security breaches. One significant threat to Wi-Fi networks is the use of tools like Nethercap to conduct Man-in-the-Middle (MitM) attacks. This study aims to explore in depth how Nethercap is used to steal Wi-Fi credentials, evaluate its impact on information security, and propose mitigation strategies. However, the convenience and flexibility offered by WiFi does not come without risks. Due to its radio wave-based nature and wide signal spread, WiFi networks are vulnerable to various security threats. In many cases, users or network administrators often neglect security aspects or are unaware of loopholes that could be exploited by malicious parties. As a result, sensitive information can be leaked, illegal access to the network can be gained, or even malicious activities can be carried out through a compromised network. Therefore, it is very important for anyone who manages or uses a WiFi network to understand the types of threats that may occur and implement appropriate solutions to maintain network security. The research method employed is descriptive qualitative with a case study approach. The analysis results show that Nethercap exploits vulnerabilities in wireless protocols, potentially leading to data theft, privacy violations, and organizational losses. Mitigation strategies include the implementation of WPA3, network segmentation, deployment of SIEM systems, and enhanced cybersecurity awareness.